MULTIPLE INTELLIGENCE AND EXAMINATION STRESS OF ANDAMAN AND NICOBAR ISLAND STUDENTS - Babu, R.; Dipti, Diana (International Journal of Psychosocial Rehabilitation, 2020)
In a highly competitive world, all the nations provide education to their citizens so that they could contribute their share in the development of the nations. It is known that intelligence is a uniform cognitive capacity possessed by an individual and Gardener’s multiple intelligence theory challenged the traditional practices in education and cognitive science. The present study is aimed to investigate the relationship between multiple intelligence and examination stress of Andaman and Nicobar Island students. The study considered a random sample of 1000 secondary students and employed the Multiple Intelligence scale and Examination stress scale to determine the correlation between multiple intelligence and examination stress. It is concluded that the level of multiple intelligence of the secondary students is high and examination stress is average based on the outcome of research also the relationship is significant.